Swimming as Treatment for Osteoporosis: A Systematic Review and Meta-analysis. (15th May 2020) - Su, Yanlin; Chen, Zhe; Xie, Wei
Abstract : Osteoporosis is a chronic disease that seriously affects human health and quality of life. This study is aimed at determining whether swimming had an effect on the bone mineral density (BMD) of the spine and femoral neck in postmenopausal and premenopausal osteoporosis patients. We retrieved relevant literature and analyzed data from randomized controlled trials to assess the effect of swimming on BMD in postmenopausal and premenopausal women. Relevant studies, with no language restrictions, from inception to September 2019, were retrieved from the PubMed, Cochrane, EMBASE, and EBSCO databases independently by two investigators. The keywords used for the literature search were "osteoporosis" and "swimming." The main results included BMD and T -score. We searched 256 relevant articles and finally screened five articles, including 263 participants. Lumbar spine density was mentioned in three articles. Although the heterogeneity of lumbar vertebral density is moderate, the analysis of swimmers to nonswimmers shows that the lumbar vertebral density in swimmers is improved [heterogeneity: ch i 2 = 5.16, df = 2 (P = 0.08 ); I 2 = 61 % ]. We analyzed the following heterogeneous subgroups: subgroup 1 (3–6 hours) and subgroup 2 (<3 hours). The BMD in subgroup 1 was significantly higher than that in the placebo, while no effect on BMD was found in subgroup 2 [heterogeneity: ch i 2 = 0.15, df = 3 (P = 0.70 ); I 2 = 0 % ]. According to the current evidence, swimming may improve the BMD of postmenopausal women participants, if the swimming time is between 3 and 6 hours, especially in long-term swimmers. However, the effectiveness of swimming does require further investigation.